Iowa Birdline update, September 16-19, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for September 16-19, 1991. The highlights for the update include sightings of a male and female Peregrine Falcon, Black-throated Blue Warbler and a Stilt Sandpiper. Also included are handwritten notes with sightings of a Piping Plover and three Semipalmated Plovers. Epson - sheet feed/flatbed